DEVELOPMENT OF THE PRODUCTION OF AN IRON OXIDE CATALYST FOR THE CONVERSION OF CARBON MONOXIDE BY WATER VAPOR - Kokanbayev Ikrаmjon Ibrokhimovich (Galaxy International Interdisciplinary Research Journal, 2023)
Synthesis gas for the production of ammonia consists mainly of hydrogen. Currently, the conversion of methane and its homologues is the main industrial method for producing synthesis gas. For this purpose, the conversion of carbon monoxide (II) is carried out in two stages on medium-temperature and low-temperature catalysts 623-823 K and 448-573 K, respectively, on modern installations; residual carbon monoxide is hydrogenated after the second stage of conversion.